Centrifugally concentric ring-patterned drug-loaded polymeric coating as an intraocular lens surface modification for efficient prevention of posterior capsular opacification. (15th January 2022) - Lu, Duoduo; Han, Yuemei; Liu, Dong; Chen, Siqi; Qie, Jiqiao; Qu, Jia; Lin, Quankui
Abstract: Posterior capsular opacification (PCO) is the main postoperative complication after intraocular lens (IOL) implantation in cataract surgery, because of the proliferation of the residual lens epithelial cells (LECs) in the lens capsule. Drug-eluting IOLs, aimed to develop an in situ drug delivery device, are the promising concept in recent years. As IOLs are optical devices other than implants, the feasibility and applicability remain a challenge for drug-eluting coatings. In this investigation, a centrifugally concentric ring-patterned drug-loaded poly(lactide-co-glycolic acid) (PLGA) coating was designed and fabricated by the spin coating technique. The concentric ring-patterned morphologies and the drug loading and release properties were carefully investigated, and the spin coating parameters were optimized. A concentric annular coating with a thin center and thick periphery was obtained, which was particularly suitable for the surface modification of IOLs, as the visual pathway of the intraocular light transmission greatly requires good light transmittance of the IOLs. IOLs with the immunosuppressant cyclosporin A (CsA)-loaded coating (CsA @ PLGA) modification were then fabricated for PCO prevention. The in vitro LECs culture results showed that the CsA @ PLGA coating-modified IOLs significantly inhibited cell proliferation and induced cell death. Western blot analysis showed that the efficient cell inhibition behavior of CsA was due to the autophagy-mediated cell death pathway. The in vivo intraocular implantation results confirmed the desired PCO inhibition effect. Thus, the centrifugally concentric ring-patterned drug-loaded PLGA coating obtained by the spin coating technique provides a simple yet effective alternative of IOL modification for PCO prevention. Statement of Significance: Concentric ring-patterned polymer coating, specifically for drug-eluting IOL fabrication, was developed by the spin coating technique. The immunosuppressant CsA inhibited LEC proliferation through the autophagy-mediated cell death pathway. Concentric ring-patterned CsA-eluting IOLs exhibited reliable in vivo PCO prevention. The drug-eluting IOLs fabricated by the simple and economical spin coating technique have a great potential in clinical translation. Graphical abstract: Image, graphical abstract